Sexual Violence Against Women in the Family: Prevention Efforts Through a Multidisciplinary Approach (Mubadalah) - Rimanto; Afriadi Bin Sanusi; Sumarni (Journal of Islamic Mubadalah, 2025)
This article is about the implementation of Mubadalah as an effort to prevent sexual violence in the family. Data shows that violence in the family is increasing and women are often victims. The purpose of this article is to analyze the model of preventing sexual violence in the household based on a multidisciplinary approach by emphasizing the concept of Mubadalah. The perspective of Mubadalah as a concept of husband and wife relations as an equal and mutually supportive relationship, which can be a foundation in dismantling patriarchal norms that perpetuate violence. This research method uses a qualitative approach, by analyzing in depth the concept of Mubadalah as an offer of resolution of household conflict, this type of article is library research with a phenomenological approach, data sources are obtained from data from the National Commission on Violence Against Women, WHO data and religious courts. The findings show that sexual violence in the household is nevertheless high due to patriarchal norms, lack of gender education, and weak law enforcement. Analysis with the Mubadalah perspective shows that relational justice and mutuality are strategic approaches in education, community empowerment, and the formulation of policies to prevent sexual violence. The results of this study indicate that the concept of Mubadalah can be integrated into education programs, legal interventions, and community-based empowerment to build just and equal families.